The Association Between Adolescent Residential Mobility and Adult Social Anxiety, BDNF and Amygdala-Orbitofrontal Functional Connectivity in Young Adults With Higher Education - Hasler, Gregor; Haynes, Melanie; Müller, Sabrina Theresia; Tuura, Ruth; Ritter, Christopher; Buchmann, Andreas (Frontiers in Psychiatry, 2020)
Background: Large-scale epidemiological studies demonstrate that house moves during adolescence increase anxiety and stress-sensitivity that persist into adulthood. As such, it might be expected that moves during adolescence have negative and long-lasting effects on the brain. We hypothesized that moves during adolescence impair fear circuit maturation, as measured by the connectivity between amygdala and orbitofrontal cortex, and expression of brain-derived neurotrophic factor (BDNF). Methods: We examined young adults with middle and high economic status recruited from the community using clinical interviews, self-report questionnaires, functional magnetic resonance imaging during an emotional faces task and during a 10 min rest phase, and serum BDNF serum concentration. Results: Out of 234 young adults, 164 did not move between ages 10 and 16 (i.e. moves with change of school), 50 moved once, and 20 moved twice or more than twice. We found relationships between adolescent moving frequency and social avoidance (pcorr=0.012), right amygdala-orbitofrontal cortex connectivity (pcorr=0.016) and low serum BDNF concentrations in young adulthood (pcorr=0.012). Perceived social status of the mother partly mitigated the effects of moving on social avoidance and BDNF in adulthood. Conclusions: This study confirms previous reports on the negative and persistent effects of residential mobility during adolescence on mental health. It suggests that these effects are mediated by impairments in fear circuit maturation. Finally, it encourages research into protecting factors of moving during adolescents such as the perceived social status of the mother.